The Role of Tungsten on the Phase Transformation Kinetics and its Correlation with the Localized Corrosion Resistance of 25Cr Super Duplex Stainless Steels. - Torres, Cristian; Hazarabedian, Maria Sofia; Quadir, Zakaria; Johnsen, Roy; Iannuzzi, Mariano (Electrochemical Society, Inc., 2020)
Super Duplex Stainless Steels (SDSS) have excellent corrosion resistance due to their high concentration of alloying elements like Cr, Mo, and N. There is still, however, disagreement on the role of tungsten in the corrosion resistance of stainless steels. In this regard, the influence of tungsten on tertiary phase precipitation kinetics remains a chief source of controversy. In this study, three different SDSS with different tungsten contents have been investigated, namely, UNS S32750 (W-free), S32760 (0.6 wt% W), and S39274 (2.1 wt% W). Different isothermal aging conditions were studied, followed by microstructure characterization using scanning electron microscopy, energy dispersive X-ray spectroscopy, electron backscatter diffraction, and transmission electron microscopy to quantify the type and volume fraction of tertiary phases and intermetallic compounds. Time-Temperature-Transformation-Corrosion maps were constructed by quantifying the changes in pitting corrosion resistance caused by the precipitation of incremental amounts of deleterious phases. Results showed that 2.1 wt% W additions retarded the precipitation kinetics of all tertiary phases—including σ-phase—favoring the formation of χ-phase. Both χ- and σ-phase affected corrosion resistance, reducing the critical pitting temperature by 10 °C–20 °C at concentrations well below 1 vol%.